New Approach to Tourist Segmentation Aimed at Regional Development (illustrated by the federal city Sevastopol’) - T. A. Voronova; I. A. Shevchuk; T. B. Melnikova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides a new approach to tourist segmentation in respect of regional policy designing. Investigation was approved on the data of selected survey of Sevastopol' guests in the period January - May 2018. The authors identified two segments - tourists and sightseers and two sub-segments - repetition of visits and accommodation. Within the frames of each segment social-demographic, economic, space and time and cultural-leisure characteristics were studied. Daily expenses of the tourist on the territory of Sevastopol' in the low season make 2,533 r., while of the sightseer - 1,741 r. 45% of tourists who arrive in the city for the first time stay in hotels, while 53% of repeated tourists stay with relatives or friends. 54% of sightseers, who arrive in the city for the first time visit 2-3 places during one day, the same program is typical of 44% of tourists staying in hotels during 3.5 days. As a result of the research opportunities to design tools of regional development were obtained. Segmentation gives a chance to identify separate contribution of tourists and sightseers to economy of the region, to find reasons for low repetition of visits or on the contrary, insufficient number of tourists and sightseers, to study motivation of the tourist concerning the place of accommodation, to assess sufficiency of cultural and leisure events.